The Influence Of Product Quality, And Brand Images On Purchasing Decisions Through The Role Of Purchase Intention As An Intervening Variable As An Intervening Variable (Case Study On Purchasing An Iphone Brand Smartphone In Yogyakarta) - Ambar Lukitaningsih; Agus Dwi Cahya; Mizan Iskandar (UNIVED Press, 2024)
This research is quantitative research, which was conducted to test the influence of product quality, brand image, and purchase intention as intervening variables on purchasing decisions. The data in this research was collected through a questionnaire using Google Form with respondents who were owners, users, or who had purchased an iPhone brand smartphone in Yogyakarta, with a total of 115 respondents. Testing in this research uses multiple linear regression analysis tests. The results of this research show that product quality has a significant effect on purchasing decisions, brand image has no effect on purchasing decisions, purchase intention has an effect on purchasing decisions. Simultaneously, the variables product quality, brand image, and purchase intention influence purchasing decisions.